From the archaeological record to virtual reconstruction : the application of information technologies at an Iron Age fortified settlement (San Chuis Hillfort, Allande, Asturias, Spain) - Salido, Juana Molina, (Archaeopress Publishing Ltd, 2018)
'From the Archaeological Record to Virtual Reconstruction' describes the use of New Information Technologies (IT) for the analyses and interpretation of archaeological record of the San Chuis Hillfort (San Martín de Beduledo, Allande, Asturias, Spain). The data gathered during the eight excavation campaigns conducted by Francisco Jordá Cerdá in the sixties and eighties of the 20th century was mechanised and digitalised. Spatial Data Infrastructure (SDI) of the hillfort was performed, followed by a creation of spatial analysis through the establishment of relations between the elements of the archaeological record. At the end, having studied and investigated the site's urban evolution throughout its occupation period (890 cal. BP-530 cal. AD), a virtual reconstruction of the hillfort in its different settlement phases, presenting various evolution scenarios, is presented.